Ammonia level as a proxy of asparaginase inactivation in children: A strategy for classification of infusion reactions. (April 2022) - Santos, Amanda C; Land, Marcelo G P; Lima, Elisangela C
Introduction: Allergic hypersensitivity reactions related to enzyme asparaginase may occur during intravenous infusion of drugs and other adverse reactions (non-allergic hypersensitivity and hyperammonemia), which do not require discontinuation of therapy as the first case. It makes differential diagnoses between infusion reactions essential to assure the team regarding the right decision to make after the adverse event. This study evaluated a pharmacovigilance strategy of differentiating infusion reactions to asparaginase in pediatric patients, based on the measurement of serum ammonia and the classification of the reactions by clinical symptoms and severity. Methodology: We included children, diagnosed with ALL, and treated with native Escherichia coli asparaginase in a university hospital. The professional team monitored and evaluated all asparaginase infusions for continuity of treatment (rechallenge), seeing the measurement of serum ammonia and classification of reactions for type and severity grade. Data from this monitoring was collected retrospectively. Chi-square and Mann-Whitney tests were used to compare the ratios between serum ammonia concentration posterior and before asparaginase infusion. Results: 245 infusions in 32 patients were monitored, and 19 reactions were observed in 17 children (53%). Three children have hyperammonemia and continue their treatment. The variation of the serum ammonia levels before and after the infusion was statistically significant, comparing the groups with no reaction or hyperammonemia versus the group with the hypersensitivity reaction. Conclusion: The pharmacovigilance strategy applied in the hospital investigated was a useful and inexpensive tool that supported clinical decision-making and enabled the maintenance of asparaginase therapy for three (9, 4%) patients followed up.